The green marketing impact on consumer buying behavior - Albanian market case study - Mariola Muçi; Endi Driza (Mednarodno Inovativno Poslovanje)
During recent years, society has been emphasizing and putting increasingly more importance on the idea of “going green” which means promoting environmentally correct and sustainable practices in the everyday life. Therefore, brands have been translating these concepts into putting out more ecological products and practices to meet the needs of the consumers and promote the importance of a greener lifestyle. These items are being developed as distinctive products to keep track of these value-conscious customers, whose consumption patterns and purchasing decisions are changing. Customers are becoming increasingly aware about environmental issues and want to get a more actively involved in reducing the environmental impact of their actions.